The Political West as the End of History - R. Sakwa (Международная аналитика, 2024)
This paper examines the enduring influence of the Political West, a power structure that emerged during the Cold War era and continues to shape international relations nowadays. Contrary to expectations of its dissolution following the collapse of the Soviet Union, the Political West expanded its influence, propelled by a belief in the ideological superiority of liberal democracy. This expansion, fuelled by notions of the “end of history,” has led to the perpetuation of Cold War dynamics, characterised by adversarial relations and ideological conflicts. The study contrasts the expectations of a post-Cold War era of positive peace with the reality of continued antagonism, exemplified by conflicts such as the Balkan wars and NATO’s interventions in Iraq and Libya. The exacerbation of tensions culminated in the onset of Cold War II in 2014, marked by proxy conflicts and, notably, the Ukrainian crisis of 2022. In response to the assertiveness of the Western political bloc, an alternative alignment led by Russia and China has emerged, challenging the unilateral dominance of Western powers. This Political East, while embodying anti-hegemonic sentiments, maintains a conservative stance within the framework of the international Charter system. The paper concludes by highlighting the fundamental transformation of international politics into a multipolar landscape. Although both the Political West and East continue to espouse the principles of the Charter, the intensification of hostilities risks destabilising the international order. In the context of the enduring Cold War dynamics and the challenges posed by global environmental change, the future of humanity is increasingly uncertain.